EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR), PROFITABILITY, AND PROFIT MANAGEMENT ON TAX EVASION - Dewi Kusuma Wardani; Ratna Monica Pricillia (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2019)
This study examines the effect of Corporate Social Responsibility (CSR), profitability, and profit management on tax evasion. We use manufacture company’s subsector food and beverage listed on the Indonesia Stock Exchange (BEI) during 2012-2016, based on purposive sampling method was obtained 8 companies. The indicators disclosure of CSR is using Global Reporting Initiative (GRI) guideline. Variable profitability is measured by a ratio of ROA, and profit management is measured by discretionary accrual. The dependent variable is proxy by CETR. We use multiple linear regression method. The result shows that the CSR and profitability have asignificant influenceon tax evasion. profit management does not have a significant influence on tax evasion.